Study on Gear Fault Diagnosis Technology based on the Method of Transmission Error - Wang Lei; Cui Yanping; Wang Yangang; Yang Yalei (Jixie chuandong)
In view of the problem of the difficulty in precise diagnosis of tooth surface fault of gear transmission system under the complicated working conduction,a fault diagnosis method based on transmission error in gear transmission system is proposed.Different gear tooth faults would make the instantaneous transmission ratio change,which affects the transmission errors of the system.The gear fault diagnosis method based on transmission error can diagnose two types of gear tooth failure including convex and concave fault through the measurement and analysis of gear transmission error signal.The experimental results show that the method is sensitive to gear tooth fault and can effectively diagnose the presence of gear faults with convex and concave in gear transmission system.